The girl with the deep blue eyes - Block, Lawrence (Hard Case Crime book, 2015)
"Cashed out from the NYPD after 24 years, Doak Miller operates as a private eye in steamy small-town Florida, doing jobs for the local police. Like posing as a hit man and wearing a wire to incriminate a local wife who's looking to get rid of her husband. But when he sees the wife, when he looks into her deep blue eyes... He falls--and falls hard. Soon he's working with her, against his employer, plotting a devious plan that could get her free from her husband and put millions in her bank account. But can they do it without landing in jail? And once he's kindled his taste for killing...will he be able to stop at one?" --